Assessment of food safety knowledge, attitudes, practices, and training of foodhandlers in the context of HACCP guidelines in Malaysian Public Universities / Lovelyna Benedict Jipiu - Benedict Jipiu, Lovelyna (Institute of Graduate Studies, UiTM, 2017)
This study aimed to assess the knowledge, attitudes, and practices (KAP) of food handlers in relation to food safety. Data collection was conducted using questionnaires that were completed by food handlers working in foodservice in public universities. Data were also collected by direct observation of food handlers performing their routines, the foodservice premises, and detection of pathogens in randomly selected food samples. Questionnaires were completed by 260 food handlers, and 130 food handlers were observed. Eleven public universities located across Malaysia were involved. Thirty-three premises were observed, and 127 randomly selected food samples were collected for pathogen detection. Rasch model analysis was used for validation, odds ratios were determined, and multivariate analysis of variance was performed to determine the relationships between the variables. The majority of the food handlers had not received any formal food safety training; therefore, they did not have a high level of general food safety knowledge, and corresponding behavioural practices were lacking. The majority of the food handlers who had completed training had higher knowledge scores than those who had not, but this was not statistically significant. Food handlers with or without training demonstrated knowledge of risks of foodborne illnesses, time and temperature abuse, improper hand washing as well as cleaning practices. Overall, food handlers‘ attitudes toward food safety were positive regardless of food safety training…